MANAGEMENT ACCOUNTING AS A TOOL FOR IMPLEMENTING CORPORATE SOCIAL RESPONSIBILITY (INNOVATIVE ECONOMY, 2026)
Bandurka M.В. MANAGEMENT ACCOUNTING AS A TOOL FOR IMPLEMENTING CORPORATE SOCIAL RESPONSIBILITYPurpose. The aim of the article is to substantiate the theoretical foundations and develop methodological tools of management accounting as a key mechanism for implementing corporate social responsibility (CSR) strategy under conditions of wartime instability, as well as to form a high-quality information base for monitoring, evaluation, and managerial decision-making in the context of sustainable development.Methodology of research. The study employs general scientific and specific methods: analysis and synthesis to generalize existing approaches to management accounting of CSR costs; a systems approach to develop a four-factor classification and an analytical cost-coding matrix, as well as to integrate social, environmental, and security aspects into the accounting system; comparative analysis to assess traditional and modern accounting models; classification to structure CSR costs; abstraction and logical generalization to formulate conceptual provisions and conclusions regarding the role of accounting information in ensuring business resilience and competitiveness.Findings. It is proven that under conditions of wartime instability, CSR expenditures acquire an investment nature and evolve into critically important factors for ensuring business resilience and continuity. The feasibility of applying strategic costing methods (ABC, target costing, lifecycle costing) is substantiated, allowing CSR costs to be distinguished from the general pool of indirect costs, linked to specific outcomes, and their impact on cost throughout the product life cycle to be assessed. An approach to constructing an analytical cost-coding matrix is developed, integrating indicators of environmental, social and security, social and humanitarian, and managerial performance (ESG components) into the overall enterprise management system.Originality. Proposals have been developed to improve management accounting for corporate social responsibility by introducing a multi-dimensional cost classification and creating a four-factor analytical matrix for their coding. For the first time, the expediency of integrating security and humanitarian components into the management accounting system under wartime conditions as core elements of the ESG approach has been substantiated.Practical value. The proposed approaches can be used by enterprises to improve accounting policies, enhance the transparency of non-financial reporting, and increase the effectiveness of managing social investments. The application of the analytical matrix enables detailed monitoring of CSR costs, assessment of their impact on business sustainability, risk reduction, and strengthening stakeholder trust.Key words: management accounting, corporate social responsibility, CSR, social responsibility costs, sustainable development, ESG, wartime economy, social costs, environmental costs, managerial decision-making.
Keywords: management accounting; corporate social responsibility; CSR; social responsibility costs; sustainable development; ESG; wartime economy; social costs; environmental costs; managerial decision-making